Simultaneous in-situ NIRS of liver and bowel during septic shock. Issue 5 (2006) - Gagnon Gagnon, R. E. R. E.; Hahum Hahum, E. E.; Skarsgard Skarsgard, E. E.; Macnab Macnab, A. J. A. J.
Abstract : We wished to use near infrared spectroscopy (NIRS) to evaluate changes in blood perfusion in the liver and small bowel. However, conventional clinical NIRS probes use adhesive light shielding appliqués that fail in direct contact with the wetness and softness of the liver and small bowel surfaces. We describe our development and testing of customized NIRS probe holders. Methods: Studies were conducted in 11 juvenile (9–17 kg) anesthetized Yorkshire piglets, with intact liver and bowel exposed during experimental septic shock induced by infusion of Escherichia coli. Internally, the emitter and detector of one NIRO-300 channel were sheathed, directed towards each other, and affixed to the opposite arms of a long-jawed ratchet clamp applied directly to the liver. The emitter and detector of the NIRO-300's second channel were applied, facing each other, on opposite inner surfaces of a semicircular, semi-rigid, reinforced rubber tube through which a loop of the small bowel was drawn. Externally, optodes from a NIRO-500 were applied to the skin over the liver. NIRS data were collected at 1second intervals for 180 minutes. Results: A wide range of optical neutral density filters was required to attenuate the emissions because of the diversity of tissue density between subjects. There were no complications with the liver clamp, and the initial tendency for the bowel to slip from the NIRS holder was solved by securing it with surgical ribbon. Conclusion: Since the NIRO-300 control algorithm did not halt monitoring; the NIRO-300 data correlated with the NIRO-500 data (r 2 =0.292 to 0.659) and both were correlated with the mean arterial blood pressure (range: r 2 =0.309 to 0.918, p < 0.05 for r 2 > 0.105), our modifications were deemed successful.